Studi Literartur Algoritma Pemograman Pada Pembelajaran Matematika - Nursania Simbolon; Yahfizham Yahfizham (Politeknik Kampar, 2023)
An algorithm is an effective step or method used to solve a particular problem or task. Algorithms are designed to be executed in a methodical manner, structured As it is. logical in this way, thus enabling consistent and efficient problem solving. A few issues that could come up during the process of designing an algorithm include: 1. Inappropriate Structure, .2. Illogical Algorithm, .3. Difficulty in Solving Algorithms: Sometimes, solving algorithms can be difficult, especially if the problem at hand is complex. This can cause confusion and require extra time to design the right algorithm. Programming algorithms typically serve as a guide for computer programmers in designing and implementing software solutions. This algorithm must be clear, systematic, and can be implemented well in the chosen programming language. This research shows that It is crucial to deal with this matter in order to plan and design the algorithm carefully. This may involve modeling the problem, logical thinking, and testing the algorithm to ensure that the algorithm is working as intended. Additionally, in software development, teams often work together to solve problems and optimize algorithms. With good practice and experience, solving algorithms can become more efficient and effective. The following are several types of programming algorithms related to mathematics: 1. Basic Mathematical Operation Algorithms, 2. Search and Sorting Algorithms, 3. Graph Algorithms 4. Geometry Algorithms, 5. Cryptographic Algorithms, 6. Statistical Algorithms, 7. Machine Learning Algorithms, 8. Advanced Mathematical Algorithms. This study uses a library approach and is qualitative.